Embolization in Trauma: Review of Basic Principles and Techniques - Lopera, Jorge E. (Seminars in Interventional Radiology, 2021)
Trauma is the leading cause of death in patients younger than 45 years. Over the last decade, there has been a progressive paradigm shift toward a nonoperative management of many blunt and penetrating injuries, placing interventional radiology in the forefront in this critical field. Transcatheter embolization is an established technique that plays a significant role in the modern treatment of traumatic injuries of the extremities, pelvis, and solid organs. The purpose of this article is to review the updated principles and techniques used in transcatheter embolization in trauma.
Keywords: embolization; trauma; transcatheter embolization; interventional radiology